PROSES PEMBELAJARAN YANG DEMOKRATIS DI SEKOLAH (STUDI DI SMA KOLESE DE BRITTO YOGYAKARTA) - Herly Janet Lesilolo (IAKN Ambon, 2020)
This study aims to explore the democratic learning process at SMA Kolese De Britto Yogyakarta as an effort to find a democratic way in the learning system in schools. The research method used in this research is naturalistic qualitative research in order to analyze learning that is democratic in a natural (natural setting). The subjects in this study were the principal, administrative staff, teachers, and students. The object of research is the overall symptoms and democratic behavior in curriculum orientation and the learning process. The subjects in this study were the principal, administrative staff, teachers, and students. The results of the research can be described as follows: 1) the democratic learning process in schools is carried out by grounding the school environment into a social world by promoting free and responsible learning processes. Teachers and students become democratic actors who free themselves from the influence of indoctrination and authority, 2) a democratic curriculum characterizes small people who live with social structures and behaviors. Upholding human rights through the human education system mechanism. Learning activities emphasize proactive dialogue through problem solving and critical thinking, group work and social skill development, and 3) the role of teachers and students, relating and interacting with mutual influence, interdependence, participation and cooperative behavior. The teacher provides a pathway for students to explore students' own values, meanings, and choices by working together to develop learning steps.